Academic Underachievement and Recovery: Student Perspectives on Effective Career Interventions. Issue 1 (March 2014) - Hwang, Mae Hyang; Lee, Donghyuck; Lim, Hyo Jin; Seon, Hye Yon; Hutchison, Brian; Pope, Mark
<x xml:space="preserve">Abstract</x> Academic achievement has a significant influence on various career development and decision‐making factors. Therefore, it is important for career counselors to understand how past academic underachievement affects students' current lives and to develop interventions that might ameliorate negative effects. This study examined the experiences of 9 ethnically diverse college students who had experienced and overcome academic failure. Data were collected by individual interviews and analyzed based on the consensual qualitative research method. Four themes emerged in relation to participants' academic underachievement and recovery: attitude, study strategies, external support, and coping difficulties. The results suggest that underachieving students are better able to cope with and overcome academic difficulties when they set clear career goals, use effective learning strategies, consciously put forth more effort, and receive external support.